Reading Freud's patients - Tzur Mahalel, Anat, author.
1 online resource.
Keywords: "What would the story of analysis look like if it were told through the eyes of the analysand? How would the patient write and present the analytic experience? How would the narrative as written by the analysand differ from the analytic narrative commonly offered by the analyst? What do the actual analytic narratives written by Freud's patients look like? This book aims to confront these intriguing questions with an innovative reading of memoirs by Freud's patients. These patients-including Sergei Pankejeff, known as the Wolf Man; the poet H. D.; and the American psychoanalyst Abram Kardiner-all came to Vienna especially to meet Freud and embark with him on the intimate and thrilling journey of deciphering the unconscious and unravelling the secrets of the psyche. A broad psychoanalytic and literary-historical reading of their memoirs is offered in this new entry to the popular Routledge History of Psychoanalysis Series, with the purpose of presenting the analysands' narratives as they themselves recounted them. This makes it possible to re-examine the links among psychoanalysis, literature, and translation and sheds new light on the complex challenge of coming to know oneself through the encounter with otherness. This book is unique in its focus on multiple memoirs by patients of Freud and presents a fresh, even startling, close-up look at psychoanalysis as a clinical practice and as a rigorous discourse and offers a new vision of Freud's strengths and, at times, defects. It will be of considerable interest to scholars of psychoanalysis and intellectual history, as well as those with a wider interest in literature and memoir"--